Perancangan Interior Pusat Rekreasi Indoor Green Park di Surabaya - Afandi, Septiany (Intra, 2015)
Indoor Green Park Recreation Center is a place that provides facilities, namely indoor garden, so that visitors can relax, relieve fatigue from work, socialize, and get information about the plant. But hoe is that plants can be grown indoors? This sceme raised the concept Taste in Nature creates modern design with natural style that can provide information to visitors and a system that supports plants indoors. In Green Park Indoor Recreation Center also include some type of support facilities to support the convenience of visitors at Green Park Indoor Recreation Centre this. Support facilities include a souvenir shop, cafÃ©, garden area, an indoor kids playground area, lobby.